Organisation of physical rehabilitation and abilitation of preschoolers with severe multiple developmental disabilities - Parfenova, L.A.; Akhmetzyanova, A.I.; Bikmukhametov, R.K. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop and justify a pedagogical model for the physical rehabilitation of children with severe multiple developmental disorders (SMDD) in preschool institutions (PI) based on a comprehensive assessment of their physical development, motor abilities, and typological characteristics. Methods and structure of the study. Analysis of scientific literature and modern approaches to physical rehabilitation (PR) of children with SMDD; descriptive experiment in three specialized preschool educational institutions; modelling of the rehabilitation and habilitation process. Results and conclusions. The theoretical and methodological foundations of PR and habilitation of children with SMDD have been defined, criteria for comprehensive assessment of physical development and motor abilities have been developed, diagnostic tools have been identified, and four typological groups of children with SMDD have been identified. A model has been developed, the conceptual basis of which is a functional approach focused on improving the body’s adaptive capabilities and forming the motor skills necessary for the daily activities of children with SMDD.